CD300f:IL-5 cross-talk inhibits adipose tissue eosinophil homing and subsequent IL-4 production - Perri Rozenberg (Nature Portfolio, 2017)
Abstract Eosinophils and their associated cytokines IL-4 and IL-5 are emerging as central orchestrators of the immune-metabolic axis. Herein, we demonstrate that cross-talk between the Ig-superfamily receptor CD300f and IL-5 is a key checkpoint that modifies the ability of eosinophils to regulate metabolic outcomes. Generation of Il5 Tg /Cd300f −/− mice revealed marked and distinct increases in eosinophil levels and their production of IL-4 in the white and brown adipose tissues. Consequently, Il5 Tg /Cd300f −/− mice had increased alternatively activated macrophage accumulation in the adipose tissue. Cd300f −/− mice displayed age-related accumulation of eosinophils and macrophages in the adipose tissue and decreased adipose tissue weight, which was associated with decreased diet-induced weight gain and insulin resistance. Notably, Il5 Tg /CD300f −/− were protected from diet-induced weight gain and glucose intolerance. These findings highlight the cross-talk between IL-5 receptor and CD300f as a novel pathway regulating adipose tissue eosinophils and offer new entry points for therapeutic intervention for obesity and its complications.